DIET DALAM PERSPEKTIF ISLAM: Kontekstualisasi Surat Al-A’raf Ayat 31 - Muhammad Hasnan Nahar; Miftah Khilmi Hidayatulloh (STAI Darul Kamal NW Kembang Kerang, 2021)
Obesity can affect anyone, arising from genetic factors or lifestyle factors. For those who experience it can cause serious problems for their health. One way to overcome this is by doing a diet, reducing excessive food consumption. In Islam the concept of diet has similarities with the prohibition of doing israf (excessive) listed in the QS. Al-A'raf verse 31 and al-bithnah, eat and drink more than what is needed. The conducting of this study is using thematic interpretation of verses about diet in Islam, the result of this study explains the concept of diet: not eating and drinking excessively, eating halal and good food, balancing types of food, avoiding haram food, eating and drinking choices. The concept of this diet can be applied by using several ways: dividing meal times, paying attention to the composition of food and staying active after eating.